Biophoton Therapy: Bioluminis Filters - Purón Sopeña, Esperanza (Revista Cubana de Física, 2017)
This work is based on the article published in the magazine Avances Médicos of Cuba, an international journal, Año XI No. 37, 36-39 (2004), and analyzes the physical concepts used on that paper to describe the mechanism of therapeutic action of the so-called Bioluminis filters. As a result of the electrical and optical measurements made on these filters, we conclude that they can not convert the incoherent light received from the sun or from environmental illumination into coherent light. We differ from the authors that the so-called coherent light, will stimulate the cell to develop the photo reactivation, which is a biophysical self reparation process, according to them, by means of a very low intensity ultraviolet light with a wavelength of 400 nm.